2021
DOI: 10.14202/vetworld.2021.483-491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peppermint oil and its microemulsion on necrotic enteritis in broiler chickens

Abstract: Background and Aim: Clostridium perfringens is one of the multiple drug-resistant intestinal pathogens causing necrotic enteritis disease, leading to great economic losses in poultry farms. This study aimed to evaluate the potential use of peppermint oil and its microemulsion (ME) as an alternative to antibiotics to control necrotic enteritis in broiler chickens. Materials and Methods: Peppermint oil ME formulation (15% oil/water) was prepared and characterized by zeta potential, Fourier transform infrared, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The effectiveness of many phytogenic compounds in reducing the incidence and severity of NE has been studied ( Table 1 ). Turmeric powder ( Ali et al, 2020 ); Yucca schidigera extract ( Calik et al, 2019 ); Origanum vulgare and Thymus vulgaris ( Timbermont et al, 2010 ); ginger oil and carvacrol; Capsicum or Curcuma longa oleoresin ( Lee et al, 2013 ); peppermint oil ( Sorour et al, 2021 ); and essential oil blends have been shown to successfully prevent C. perfringens and improve broiler efficiency ( Gharaibeh et al, 2021 ).…”
Section: Intervention Strategies For Nementioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of many phytogenic compounds in reducing the incidence and severity of NE has been studied ( Table 1 ). Turmeric powder ( Ali et al, 2020 ); Yucca schidigera extract ( Calik et al, 2019 ); Origanum vulgare and Thymus vulgaris ( Timbermont et al, 2010 ); ginger oil and carvacrol; Capsicum or Curcuma longa oleoresin ( Lee et al, 2013 ); peppermint oil ( Sorour et al, 2021 ); and essential oil blends have been shown to successfully prevent C. perfringens and improve broiler efficiency ( Gharaibeh et al, 2021 ).…”
Section: Intervention Strategies For Nementioning
confidence: 99%
“…Reduces colony-forming units and improved growth performance. Sorour et al, 2021 Oregano ( Origanum vulgare subsp. hirtum ) 10 g/kg No experimental infection.…”
Section: Intervention Strategies For Nementioning
confidence: 99%
“…Peppermint oil 0.5 or 0.25 ml/ml of water Reduction in mortality (55% PC vs 10% EOs). Improve BWG in 41 g ND € [138] Thymol and carvacrol 120 mg/kg of feed Reduction in mortality (20% PC vs 4% EOs). >2 vs <1 (PC vs EOs).…”
Section: Vs 10 (Pc Vs Eos)mentioning
confidence: 99%
“…To characterise the nanoemulsion and measure electrical conductivity, viscosity , zeta potential (surface charge) by the Zeta device NANOTRAC-WAVE II Zetasizer (MICROTRAC, USA) and to determine the size of the droplet and the distribution of the microemulsion (polydispersity indexes PDI), transmission electron microscopy (TEM) monitoring is used (JEM (1400F) HRTEM) at ray power of (300) keV . acc ording to 20 .…”
Section: Preparation and Characterization Of Nanoemulsionmentioning
confidence: 99%